Biology and morphometrics of the immature stages of Epinotia aporema on artificial diet - Arneodo, Joel; Quintana, Graciela; Sciocco-Cap, Alicia (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to establish a life table for the immature stages of Epinotia aporema, as part of a wider investigation on its biological control. Insects were reared on an artificial diet at 25±1ºC and a 16:8 (light:dark) hour photoperiod. For the identification of larval instars for the study of pathogen-insect interactions under laboratory conditions, head capsule widths (HCWs) were also determined. The egg incubation period was 4.13±0.30 days, larval stage took 11.64±0.49 days, and the development time of the pupal phase was sex-dependent with 8.51±0.69 days for the females and 9.41±0.65 days for the males. Five larval instars were identified.